The Dark Triad Traits and the Prediction of Eudaimonic Wellbeing - Liu, Yaqian; Zhao, Na; Ma, Min (Frontiers in Psychology, 2021)
Although numerous studies have focused on personality traits related to well-being, the relationship between the Dark Triad Traits and eudaimonic well-being is still unclear. The purpose of the present study is to explore how the Dark Triad Traits (i.e., narcissism, Machiavellianism, and psychopathy) affect eudaimonic well-being. Further, this study also aims to explore the mediation effect of family support and hedonic well-being. The results showed that the present model had a good model fit (χ2/df = 1.91, p < .001, CFI = .96, TLI = .95, RMSEA = .04, SRMR = .04). There is a significant association between the Dark Triad Traits and eudaimonic well-being. Specifically, narcissism directly predicts eudaimonic well-being, while the effects of Machiavellianism and psychopathy on eudaimonic well-being are serial two-mediator models, which are mediated by family support and hedonic well-being. The results would enrich theoretical studies on personality, while provide some practical evidence on how to improve individuals’ subjective well-being.